Noel Bamford: the first director of the Auckland School of Architecture - Tyler, Linda (Architectural History Aotearoa, 2022)
Auckland's keenest advocate of the Arts and Crafts movement was Frederick Noel Bamford (1881-1952) who was the first director of the Auckland School of Architecture from 1917-19. Apprenticed to carpenter and architect Edward Bartley (1839-1919) during the years that St Matthews-in-the-city was being designed, Bamford excelled at drawing and travelled to London to become a student at the Royal Institute of British Architects' School in 1904. Along with fellow expatriate architectural student Arthur Patrick Hector Pierce (1879-1918), Bamford found work in the office of Edwin Lutyens (1869-1919), famed for his romantic English country houses. Bamford returned to Auckland in 1906, and was elected an Associate of the RIBA the following year. Pierce followed, and they formed an architectural partnership which became renowned for its houses in the English Domestic Revival style adapted for New Zealand conditions. Bamford and Pierce are best known for designing the glamourous Coolangatta, 464 Remuera Road (1911, demolished in 2006) for Canadian-born Alfred Foster, a surveyor and his wife Jessie, which Peter Shaw observes is almost an exact copy of a Lutyens house at Fulbrook, Elstead, Surrey, built in 1897. As well as indicating the rapid transmission the Lutyens country house typology to New Zealand, the story of the Bamford and Pierce partnership offers an intriguing insight into the social relationships of Edwardian Auckland. Pierce's father George was prominent in the Anglican Diocese, and one of the earliest commissions that Bamford and Pierce secured was for Bishopscourt, a home for the Anglican Bishop of Auckland, known as Neligan House (1909-10). Connections to the law firm of Hesketh Richmond (Bamford's father was Edwin Bamford, (1846-1928), Registrar-General of Lands) resulted in the commission for Waione (1910), a single storey house at 22 Domett Avenue, Epsom as well as two houses for wealthy heiress Jeannie Stirling Richmond (1854-1917) for construction on her Rockwood estate. Ngahere at 74 Mountain Road (1907-8) was designed for Richmond's newly married daughter Margaret MacCormick (1884-1972) is renowned for its butterfly floor plan. Woodend at Gilgit Road (circa 1914-15) was designed as the home of Noel Bamford's brother, lawyer Dr Harry Dean Bamford, who lectured in law at Auckland University College. In 1912, the year that his Remuera house went up in flames destroying £2000 worth of Arts and Crafts furniture, Bamford founded the Arts and Crafts Club in Auckland, becoming its inaugural president. The Club was to have a key role in promoting the adaptation of the ideology of William Morris, and incorporated Māori arts into its definition of craft.